2022
DOI: 10.3389/fmicb.2022.920109
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Variation in the Phyllospheric Microbial Biodiversity of Alternaria Alternata-Infected Tobacco Foliage

Abstract: Phyllospheric microbial composition of tobacco (Nicotiana tabacum L.) is contingent upon certain factors, such as the growth stage of the plant, leaf position, and cultivar and its geographical location, which influence, either directly or indirectly, the growth, overall health, and production of the tobacco plant. To better understand the spatiotemporal variation of the community and the divergence of phyllospheric microflora, procured from healthy and diseased tobacco leaves infected by Alternaria alternata,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 75 publications
3
12
0
Order By: Relevance
“…Moreover, the number of fungal OTUs in the healthy groups (treated and untreated) was higher than the diseased groups (Chen et al, 2020;Huang et al, 2021b). These results are in line with previous reports indicating higher OTUs in healthy samples compared to diseased samples (Dai et al, 2022). The diversity and richness of the fungal communities in the healthy groups were higher than the disease-causing G. cichoracearum DC (Huang et al, 2020)d segeticola-infected tobacco leaves (Huang et al, 2021b).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, the number of fungal OTUs in the healthy groups (treated and untreated) was higher than the diseased groups (Chen et al, 2020;Huang et al, 2021b). These results are in line with previous reports indicating higher OTUs in healthy samples compared to diseased samples (Dai et al, 2022). The diversity and richness of the fungal communities in the healthy groups were higher than the disease-causing G. cichoracearum DC (Huang et al, 2020)d segeticola-infected tobacco leaves (Huang et al, 2021b).…”
Section: Discussionsupporting
confidence: 89%
“…It could be said that Candida could possibly emerge as a secondary infective agent once the plant becomes susceptible to TBS. The top 10 genera causing tobacco leaf infections include Golovinomyces cichoracearum DC (Huang et al, 2020), Didymella segeticola (Huang et al, 2021b), A. alternata (Dai et al, 2022); the genera that cause asymptomatic and symptomatic infections in tobacco leaves (Xiang et al, 2022) include Alternaria, Cladosporium, Phoma and Boeremia. Generally, these genera are detected during the maturation period of tobacco and form the core fungal microbiome of tobacco phylloplane.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco’s leaves are continually subjected to excessive strong sunlight on summer days, which makes it an ideal material to study the mechanism of bacterial community assembly and succession in the face of strong abiotic stresses (i.e., UV radiation, desiccation and heat), accompanied with pathogen invasion ( Bringel and Couée, 2015 ; Xing et al., 2022 ). Dai et al. (2022) investigated the spatiotemporal variation of the community tobacco leaves affected by brown spot disease and found that the relative abundance of Pseudomonas, Sphingomonas , and Methylobacterium increased as tobacco leaves aging gradually.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive understanding of these interactions is necessary for predicting disease incidence and severity and finding novel solutions against them. For example, Dai et al. (2022) investigate the spatiotemporal changes in community tobacco leaves infected by brown spot disease.…”
Section: Introductionmentioning
confidence: 99%